DEVELOPMENT AND VALIDATION OF UV SPECTROPHOTOMETRIC AND REVERSED PHASE‑HIGH PERFORMANCE LIQUID CHROMATOGRAPHY ‑ PDA METHODS FOR THE ESTIMATION OF ALOGLIPTIN BENZOATE - P, SUPRIYA; N, MADHAVI LATHA; KBV, ROHITH; GV, RAMANA; U, HARINI; AKM, PAWAR (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To develop and validate simple, rapid, precise, accurate, and economical UV spectrophotometric and reverse phase high performance liquid chromatographic methods for the estimation of alogliptin benzoate (AGP). Methods: UV spectrophotometric method was performed using UV/Vis double beam spectrophotometer with a spectral bandwidth of 1 nm and 1.0 cm matched quartz cells. The maximum absorbance of AGP was observed at 276 nm using methanol as solvent. Reversed phase-high performance liquid chromatography (RP-HPLC) method was carried out on a Unisol reverse phase C18 column (150 mm × 4.6 mm, 3 μm) with a mobile phase composed of methanol and 10 mM ammonium acetate buffer (adjusted to pH 5.0 with glacial acetic acid) in the ratio of 80:20 v/v with a flow rate of 0.8 ml/minutes. Results: The linearity of methods was found to be in the range of 5-35 µg/ml (UV) and 20-100 µg/ml (RP-HPLC) and the correlation coefficient was 0.999 for both the methods. The regression equations were y = 0.028x + 0.023 (UV) and y = 28,58,942x - 4,33,647 (HPLC). The retention time of AGP was 2.37 minutes. Conclusion: The proposed methods were validated in terms of linearity, precision, accuracy, specificity, robustness, limit of detection, and limit of quantitation as per International Conference on Harmonization Q2 R1 guidelines. Thus, the proposed methods are novel, sensitive, and reliable and can be successfully used for the quantitation of AGP. Keywords: Alogliptin benzoate, UV-visible spectrophotometer, Reversed phase-high performance liquid chromatography, International Conference on Harmonization guidelines.